Semantic Exploration of Emotional Contrast in “Last Christmas” by Wham! - Nerin Sry Rahayu; Dimas Adika (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2025)
This research aims to examines emotional contradictions in Wham!'s “Last Christmas” through semantic analysis and conceptual metaphors. Using a qualitative descriptive method, six respondents without formal music education provided emotional perceptions of the song. The lyrics, centered on loss and betrayal, employ metaphors like “I gave you my heart” to convey trust and vulnerability. In contrast, the upbeat melody fosters a positive atmosphere, enhancing the emotional complexity for listeners. Findings highlight how metaphors help conceptualize abstract emotions, while the melody emphasizes emotional contrasts. This interplay between lyrics and melody transforms “Last Christmas” into a reflective artistic piece, offering deeper insights into emotional expression and contributing to the study of music-emotion relationships.